Impact of dairy cooperatives on input and energy use of milk production in Punjab - sharma, vk (Indian Journal of Dairy Science, 2018)
Sri Muktsar Sahib District falls in the South-Western region of Punjab which was facing the problems of periodic cotton crop failures and the water logging. The uncertainty of income from the crop sub-sector forced the farmers to shift towards dairy to earn regular income for their livelihoods. Therefore the task of milk cooperative societies assumed the prime importance to streamline the production and marketing of milk. The results of the study clearly indicated that the overall total input use per milch animal per annum by member was Rs.81402 and overall total input use by non member group was Rs.82501. Overall total energy use per milch animal per annum by member group was less (Rs.730) as compared to non member group (Rs.761). The overall total costs of maintaining a milch animal per annum came out to be Rs.98626 in member group which were less as compared to non member group Rs. 101069.